Structure-tuned membrane active Ir-complexed oligoarginine overcomes cancer cell drug resistance and triggers immune responses in mice. Issue 34 (10th August 2020) - Ji, Shuangshuang; Yang, Xiuzhu; Chen, Xiaolong; Li, Ang; Yan, Doudou; Xu, Haiyan; Fei, Hao
Abstract : Structure optimized Ir-complexed cyclic octa-arginine shows a potential of "one-drug two-effects" for cancer treatment. Abstract : The development of chemotherapy, an important cancer treatment modality, is hindered by the frequently found drug-resistance phenomenon. Meanwhile, researchers have been enthused lately by the synergistic use of chemotherapy with emerging immunotherapeutic treatments. In an effort to address both of the two unmet needs, reported herein is a study on a series of membrane active iridium(iii ) complexed oligoarginine peptides with a new cell death mechanism capable of overcoming drug resistance as well as stimulating immunological responses. A systematic structure–activity relationship study elucidated the interdependent effects of three structural factors, i.e., hydrophobicity, topology and cationicity, on the regulation of the cytotoxicity of the Ir(iii )-oligoarginine peptides. With the most prominent toxicities, Ir-complexed octaarginines (R8) were found to display a progressive oncotic cell death featuring cell membrane-penetration and eruptive cytoplasmic content release. Consequently, this membrane-centric death mechanism showed promising potential in overcoming multiple chemical drug-resistance of cancer cells. More interestingly, the eruptive mode of cell death proved to be immunogenic by stimulating the dendritic cell maturation and inflammatory factor accumulation in mice tumours. Taking these mechanisms together, this work demonstrates that membrane active compounds may become the next generation chemotherapeutics because of their combined advantages.